Controversy over "Jullien, " or where and what is China, Philosophically Speaking?. Issue 3 (September 2014) - Weber, Ralph
Abstract: This article is about François Jullien and a controversy that arose over the publication of a pamphlet by Jean François Billeter entitled Against François Jullien, replied by Jullien in a volume subtitled Reply to *** (the asterisks standing for Billeter) and followed by collections of essays by French (and some German) intellectuals—one of them entitled For Jullien . The controversy assumed a weight that went beyond Jullien and the French debate to the heart of sinology and also of philosophy. The question, what and where China is philosophically speaking, is discussed with regard to the role of context, the notion of heterotopy, and the political side of talk about China.